Cytotoxicity of Vibrio parahaemolyticus AHPND toxin on shrimp hemocytes, a newly identified target tissue, involves binding of toxin to aminopeptidase N1 receptor. - Waruntorn Luangtrakul; Pakpoom Boonchuen; Phattarunda Jaree; Ramya Kumar; Han-Ching Wang; Kunlaya Somboonwiwat (PLoS Pathogens, 2021)
Acute hepatopancreatic necrosis disease (AHPND) caused by PirABVP-producing strain of Vibrio parahaemolyticus, VPAHPND, has seriously impacted the shrimp production. Although the VPAHPND toxin is known as the VPAHPND virulence factor, a receptor that mediates its action has not been identified. An in-house transcriptome of Litopenaeus vannamei hemocytes allows us to identify two proteins from the aminopeptidase N family, LvAPN1 and LvAPN2, the proteins of which in insect are known to be receptors for Cry toxin. The membrane-bound APN, LvAPN1, was characterized to determine if it was a VPAHPND toxin receptor. The increased expression of LvAPN1 was found in hemocytes, stomach, and hepatopancreas after the shrimp were challenged with either VPAHPND or the partially purified VPAHPND toxin. LvAPN1 knockdown reduced the mortality, histopathological signs of AHPND in the hepatopancreas, and the number of virulent VPAHPND bacteria in the stomach after VPAHPND toxin challenge. In addition, LvAPN1 silencing prevented the toxin from causing severe damage to the hemocytes and sustained both the total hemocyte count (THC) and the percentage of living hemocytes. We found that the rLvAPN1 directly bound to both rPirAVP and rPirBVP toxins, supporting the notion that silencing of LvAPN1 prevented the VPAHPND toxin from passing through the cell membrane of hemocytes. We concluded that the LvAPN1 was involved in AHPND pathogenesis and acted as a VPAHPND toxin receptor mediating the toxin penetration into hemocytes. Besides, this was the first report on the toxic effect of VPAHPND toxin on hemocytes other than the known target tissues, hepatopancreas and stomach.